Socio-emotional characteristics in early childhood and offending behaviour in adolescence - Garcia, Paul (International Journal of Population Data Science, 2026)
Early cognitive and socio-emotional development are key determinants of later life outcomes. This paper examines how socio-emotional characteristics identified in early childhood are associated with offending behaviour during adolescence, using de-identified, linked administrative data from the Ministry of Justice and the Department for Education. This linkage also allows us to follow pupils across compulsory schooling and to examine how school outcomes such as persistent absenteeism, exclusions, and attainment shape offending. Children who go on to offend display lower early development scores overall. Cognitive difficulties are largely explained by later school challenges, but socio-emotional difficulties remain strong predictors of offending even after accounting for school outcomes. The analysis also indicates that children with extreme developmental difficulties are less likely to engage in offending than those with moderate difficulties. This may be because severe difficulties reduce the likelihood of offending by limiting opportunities or by triggering early intervention through Special Education Needs (SEN) services or Social Care. By identifying these early risk indicators, the research underscores the need for tailored interventions. Cognitive difficulties appear to influence offending primarily through school experiences and may be best addressed with school-based support. Socio-emotional difficulties operate more independently and call for family- and community-based approaches. Together, these insights contribute to policies and practices that better support children’s development and reduce the likelihood of future offending.